Performance Analysis of a Relift Luo Converter-Derived Dual-Output DC to DC Converter for Microgrid Applications - R. Banupriya; R. Nagarajan (International Journal of Photoenergy)
A microgrid typically maintains multiple voltage bus bars with AC or DC or both. The various subsystems participating in the microgrid are connected to the appropriate voltage bus bars. Renewable energy sources like the wind energy or the solar photovoltaic energy may also be integrated to the microgrid. A battery-based energy storage system is also usually required. In this work, a dual-output DC to DC converter derived from the double lift or the relift Luo converter is proposed and validated. The proposed system uses a solar photovoltaic source and delivers a high-voltage DC output to deliver power to the high-voltage DC bus bar. A battery of medium voltage is connected across the second output of the dual-output converter. The proposed idea is validated using modeling and simulations in the MATLAB Simulink environment and an experimental prototype.